Mechanisms of Action and Reduced Cardiotoxicity of Pixantrone; a Topoisomerase II Targeting Agent with Cellular Selectivity for the Topoisomerase IIα Isoform - Hasinoff, Brian B. (J Pharmacol Exp Ther, 2016)
Pixantrone is a new noncardiotoxic aza-anthracenedione anticancer drug structurally related to anthracyclines and anthracenediones, such as doxorubicin and mitoxantrone. Pixantrone is approved in the European Union for the treatment of relapsed or refractory aggressive B cell non-Hodgkin lymphoma. This study was undertaken to investigate both the mechanism(s) of its anticancer activity and its relative lack of cardiotoxicity. Pixantrone targeted DNA topoisomerase IIα as evidenced by its ability to inhibit kinetoplast DNA decatenation; to produce linear double-strand DNA in a pBR322 DNA cleavage assay; to produce DNA double-strand breaks in a cellular phospho-histone γH2AX assay; to form covalent topoisomerase II-DNA complexes in a cellular immunodetection of complex of enzyme-to-DNA assay; and to display cross-resistance in etoposide-resistant K562 cells. Pixantrone produced semiquinone free radicals in an enzymatic reducing system, although not in a cellular system, most likely due to low cellular uptake. Pixantrone was 10- to 12-fold less damaging to neonatal rat myocytes than doxorubicin or mitoxantrone, as measured by lactate dehydrogenase release. Three factors potentially contribute to the reduced cardiotoxicity of pixantrone. First, its lack of binding to iron(III) makes it unable to induce iron-based oxidative stress. Second, its low cellular uptake may limit its ability to produce semiquinone free radicals and redox cycle. Finally, because the β isoform of topoisomerase II predominates in postmitotic cardiomyocytes, and pixantrone is demonstrated in this study to be selective for topoisomerase IIα in stabilizing enzyme–DNA covalent complexes, the attenuated cardiotoxicity of this agent may also be due to its selectivity for targeting topoisomerase IIα over topoisomerase IIβ.